Effects of soy lecithin and distilled monoglyceride in combination with tallow on nutrien digestibility, serum lipids, and growth performance in weanling pigs - Jones, D.B.; Hancock, Joe D.; Walker, Charles E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Four hundred twenty pigs (21 d of age and 12.3 lb avg initial wt) were used to determine if adding soybean oil, lecithin, and monoglyceride to diets containing tallow affects nutrient digestibility, serum lipids, and growth performance. Treatments were: 1) a high nutrient density diet (HNOD) with 10% soybean oil; 2) HNDD with 10% tallow; 3, 4, and 5) diet 2 with 9% tallow and 1% soybean oil, lecithin, and monoglyceride, respectively. Adding soybean oil, lecithin, and monoglyceride to tallow increased digestibility of total fat, longchain saturated fatty acids, and medium-chain fatty acids, but reduced serum concentrations of triglycerides and total, HDL (high density lipoprotein), and LDL (low density lipoprotein) cholesterol. From d 0 to 14, pigs fed soybean oil had greater ADG and ADFI than pigs fed the other treatments, and pigs fed tallow without emulsifiers had the lowest ADFI. From d 0 to 7 and 0 to 14, pigs fed diets with lecithin had improved F/G compared to pigs fed monoglyceride. For d 0 to 35, fat source or emulsitier treatment did not affect growth performance. The addition of emulsifiers increased digestibility of tallow but had only small effects on growth performance early in the nursery phase.
Keywords: Swine; Starter; Digestibility; Growth; Soybean oil; Tallow; Lecithin; Monoglyceride